Transformation of health system in Ecuador - Jiménez Barbosa, Wilson Giovanni; Granda Kuffo, María Luisa; Ávila Guzmán, Diana Margoth; Cruz Díaz, Leidy Johanna; Flórez Parra, Julián Camilo; Mejía, Luisa Silvana; Vargas Suárez, Diana Carolina (Universidad y Salud, 2017)
Objective: To describe the transformations of the structure of the health system in Ecuador, taking into account the constitutional and policy context of that country, and to reflect on the historical context in which it occurred and its implications for the welfare of the people from Ecuador. Materials and methods: A bibliographic review was made, beginning with the regulations of Ecuador since the Constitution of 1979, where health is considered as a right, passing by the Organic Law of Health, the Social Security Act, among others, including the last reform of the Constitution in 2008. Results: The transformation of the Health System of Ecuador is the result of the action of economic and political forces, both internal and external, that have affected this country throughout the studied period.